(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Feminism is reflected in literature as well as other works in western nations, but due to the oraltradition and increased illiteracy in the east, especially in countries such Asindia, the influence of thesestudies was limited to the urban population. Aside from the current Indian ring ages, Indian ladies havebeen writing in English for a long time. Poets, novelists, playwrights, short story authors, and reviewersare no longer behind their male colleagues. Their literary work has earned a permanent position in theanthology of global literature. They have made a substantial contribution to the richness of Indian Englishworks, notably in the fiction category. India’s female authors have reached the pinnacle of their careersand have gained international acclaim.